PICK'S FORMULA AND GENERALIZED EHRHART QUASI-POLYNOMIALS - Takayuki Hibi; Miyuki Nakamura; Ivana Natalia Kristantyo Samudro; Akiyoshi Tsuchiya (Journal of the Indonesian Mathematical Society, 2015)
By virtue of Pick's formula, the generalized Ehrhart quasi-polynomial of the triangulation $\mathcal{P} \subset \mathbb{R}^2$ with the vertices $(0,0), (u(n),0), (0,v(n))$, where $u(x)$ and $v(x)$ belong to $\mathbb{Z}[x]$ and where $n=1,2, …$, will be computed.DOI : http://dx.doi.org/10.22342/jims.21.2.192.71-75